Implementasi E-Government pada Dinas Koperasi dan Ukm Provinsi Jambi - Bakti Ramadhani; Besse Wediawati; Dessy Elliyana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to analyze the implementation of e-government at the Jambi Province Cooperatives and SMEs Office and identify the factors influencing its implementation based on George Edward III’s policy implementation theory. The research employed a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation involving office personnel and community service users as informants. The findings indicate that the implementation of e-government has not yet been optimal in supporting the delivery of digital-based public services. Several factors contribute to this condition, including ineffective communication and dissemination of information to the public, limited human resources with adequate technological competencies, implementers’ attitudes that are not fully adaptive to technological changes, and a bureaucratic structure that has not supported comprehensive system integration. These challenges affect the efficiency, accessibility, and quality of public services provided by the agency. Furthermore, the study highlights the importance of strengthening coordination among stakeholders and improving institutional readiness in implementing digital governance. The study concludes that efforts to improve human resource capacity, enhance public outreach, and develop an integrated information system are essential to optimize e-government implementation and improve the quality, effectiveness, and responsiveness of public services in the digital era.